IMPROVING LISTENING SKILL OF REPORT TEXT THROUGH LEARNING CELL AND PINACOY - Kuswahyuningsih Kuswahyuningsih (UIN Raden Mas Said Surakarta, 2017)
A lot of students encounter obstacles in mastering listening skill of report text. The goals of study are to describe the influence of applying learning cell and utilizing of Pinacoy toward listening skill especially in report text of Second Year Students of Social Program in MAN Sukoharjo. The study is also to describe the students’s listening ability of applying Learning cell and the utilizing of Pinacoy .The technique is utilized to collect the data in this study is classroom action research. The data validity of this study uses interview, observation, and test. The results of study are that there are influence of applying learning cell and the utilizing of Pinacoy toward listening skill especially in report text and the average of students’ scores can reach KKM (passing grade standard) after the researcher applied learning cell and utilized Pinacoy toward listening skill.